Hybrid Leadership in the Implementation of a Love-Based Curriculum: Transformational Integration and Servant Leadership - Nur Faizah (ICM Research (Yayasan Insan Cendekia Mandalika), 2026)
Islamic educational institutions today face significant challenges in responding to relational crises and value fragmentation amid the unstoppable wave of modernization. The Love-Based Curriculum (Kurikulum Berbasis Cinta/KBC) offers a humanistic educational approach that positions compassion, respect for human dignity, and dialogic relationships as the cornerstone of the learning process. Yet, its successful implementation depends critically on a leadership model capable of fostering organizational culture change while sustaining the depth of human relationships. This study employed a qualitative approach using a single case study design and phenomenological lens. Data were gathered through semi-structured in-depth interviews with ten informants, ten days of participatory observation, and document analysis. Data analysis followed the Miles, Huberman, and Saldaña interactive model encompassing data condensation, data display, and conclusion drawing and verification. The findings reveal that the principal of MA Al-Jauhariyah simultaneously and organically enacts hybrid leadership. The transformational dimension manifests in building a collective vision, stimulating pedagogical innovation, and demonstrating moral exemplification; while the servant leadership dimension is evident in listening leadership, empathetic mentoring, meaningful teacher empowerment, and the cultivation of a values-based community. The integration of both approaches forms a leadership model that is not only visionary, but also deeply humanistic and rooted in rahmah values within Islamic education. The hybrid model characterized by visionary-relational synchrony, a change-value preservation dialectic, trust-based leadership distribution, and leadership reflexivity contributes theoretically to hybrid leadership scholarship in the madrasah context, while offering a practical guide for the systematic and sustainable implementation of value-based curricula.